Etiology of hormone receptor positive breast cancer differs by levels of histologic grade and proliferation. Issue 4 (25th March 2018) - Abubakar, Mustapha; Chang‐Claude, Jenny; Ali, H. Raza; Chatterjee, Nilanjan; Coulson, Penny; Daley, Frances; Blows, Fiona; Benitez, Javier; Milne, Roger L.; Brenner, Hermann; Stegmaier, Christa; Mannermaa, Arto; et al.
Abstract : Limited epidemiological evidence suggests that the etiology of hormone receptor positive (HR+) breast cancer may differ by levels of histologic grade and proliferation. We pooled risk factor and pathology data on 5, 905 HR+ breast cancer cases and 26, 281 controls from 11 epidemiological studies. Proliferation was determined by centralized automated measures of KI67 in tissue microarrays. Odds ratios (OR), 95% confidence intervals (CI) and p ‐values for case–case and case–control comparisons for risk factors in relation to levels of grade and quartiles (Q1–Q4) of KI67 were estimated using polytomous logistic regression models. Case–case comparisons showed associations between nulliparity and high KI67 [OR (95% CI) for Q4 vs . Q1 = 1.54 (1.22, 1.95)]; obesity and high grade [grade 3 vs . 1 = 1.68 (1.31, 2.16)] and current use of combined hormone therapy (HT) and low grade [grade 3 vs . 1 = 0.27 (0.16, 0.44)] tumors. In case–control comparisons, nulliparity was associated with elevated risk of tumors with high but not low levels of proliferation [1.43 (1.14, 1.81) for KI67 Q4 vs . 0.83 (0.60, 1.14) for KI67 Q1]; obesity among women ≥50 years with high but not low grade tumors [1.55 (1.17, 2.06) for grade 3 vs . 0.88 (0.66, 1.16) for grade 1] and HT with low but not high grade tumors [3.07 (2.22, 4.23) for grade 1 vs . 0.85 (0.55, 1.30) for grade 3]. Menarcheal age and family history were similarly associated with HR+ tumors of different grade or KI67 levels. These findings provide insights into the etiologic heterogeneity of HR+ tumors. Abstract : What's new? Limited epidemiological evidence suggests that the etiology of hormone receptor positive (HR+) breast cancer may differ by HR+ tumor subtypes as defined by histologic grade and proliferation level. In this report pooling risk factor data from a consortium of breast cancer studies, the authors found associations between nulliparity and highly proliferative tumors; obesity and high grade tumors; and current use of combined hormone therapy and low grade tumors. These results provide insights into heterogeneity of HR+ tumors that may be reflective of differences in etiological pathways, and could also have implications for risk prediction of aggressive subtypes of HR+ tumors.